2012
DOI: 10.1590/s0037-86822012000600017
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions following mass drug administration with diethylcarbamazine in lymphatic filariasis endemic areas in the Northeast of Brazil

Abstract: Introduction:The Global Programme to Eliminate Lymphatic Filariasis was launched with the goal of eliminating this disease via the annual mass drug administration (MDA) of a single dose of antifilarial drugs. Adverse drug reactions following MDA are a major factor of poor treatment adherence in several countries. This study assessed the occurrence of adverse drug reactions (ADRs) following the first round of mass treatment in two communities treated with different dosages of diethylcarbamazine (DEC) in the Cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Localized AEs following LF treatment are much less common than systemic AEs. They include the development of subcutaneous or scrotal nodules, spermatic cord swelling, new onset or increased hydrocele, dilated and inflamed lymphatic vessels (the “string sign”) [ 68 ], arthritis, lymphadenitis (sometimes with suppuration), and new onset lymphedema [ 76 ]. Local reactions may occur within 24–48 hours after treatment, but often the onset is later (1 week or more after treatment) [ 15 , 17 , 44 , 45 , 55 , 59 , 66 , 72 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Localized AEs following LF treatment are much less common than systemic AEs. They include the development of subcutaneous or scrotal nodules, spermatic cord swelling, new onset or increased hydrocele, dilated and inflamed lymphatic vessels (the “string sign”) [ 68 ], arthritis, lymphadenitis (sometimes with suppuration), and new onset lymphedema [ 76 ]. Local reactions may occur within 24–48 hours after treatment, but often the onset is later (1 week or more after treatment) [ 15 , 17 , 44 , 45 , 55 , 59 , 66 , 72 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, two community MDA studies with passive AE surveillance reported higher rates in women. This may reflect gender-specific differences in reporting, rather than physiologic differences [ 76 , 92 ]. In one large MDA study in Haiti, moderate AEs (those interfering with school or work) were more frequently reported by men, and these were most commonly due to scrotal pain [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since most of the excess AEs in females were of severity grade 1, it is possible that females were more likely than males to report mild AEs. Other studies have reported increased AE rates in females following MDA [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Increased adverse events/side effects directly due to the higher dose of albendazole or as a result of interaction with DEC could be a limiting factor to deployment [ 16 , 17 , 18 , 19 ]. However, 800mg albendazole has been extensively used for longer periods for systemic helminth infections such as echinococcosis and neurocysticercosis and is generally well tolerated [ 20 ].…”
Section: Discussionmentioning
confidence: 99%